Use of ozone therapy as a treatment of pathologies in small animals (Revista Sistemas de Producción Agroecológicos, 2019)
In this monographic work a literature review is made on the current state of ozone therapy in the small animal clinic is carried out. Initially ozone was used for the treatment and purification of water and since 1915 began to be used as a therapeutic agent in people for their germicidal action. In human medicine the effects of ozone on the body have been recognized, such as balance in REDOX balance, oxygen metabolism improvement, immunomodulatory effect, anti-inflammatory properties, analgesic action, healing promoter and germicidal action. All of its properties are directly related to the generation of by-products, reactive oxygen species (ROS) and Lipid Oxidation Products (LOPs), which in adequate amounts produce such biological processes. In the small animal clinic, ozone therapy is being used mainly in the treatment of bacterial, fungal and ectoparasitic diseases affecting the skin. Studies have also been made of its efficacy in the management of pain in musculoskeletal conditions, especially chronic ones. Ozone in Veterinary Medicine has a promising future and has great potential for further studies on small animals.
Keywords: ozone; ozone therapy; immunomodulator; oxygen; reactive oxygen species; lipid oxidation products